ANALISIS PENERIMAAN PAJAK BAHAN BAKAR KENDARAAN BERMOTOR SEBELUM DAN SETELAH KENAIKAN HARGA BBM PADA TAHUN 2022 TERHADAP KONTRIBUSI PENDAPATAN PAJAK DAERAH DI SULAWESI UTARA - Macpal, Marchela Kezia; Kalangi, Lintje; Weku, Priscillia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Regional taxes are one source of revenue that funds existing development, one type of regional tax is motor vehicle fuel tax. This type of research is qualitative with descriptive methods. This research aims to (1) determine motor vehicle fuel tax revenues before and after the fuel price increase in 2022 in North Sulawesi (2) determine the contribution of motor vehicle fuel tax revenues before and after the fuel price increase in 2022 to regional tax revenues in North Sulawesi (3) understand efforts to increase motor vehicle fuel tax revenue in North Sulawesi. The data source is primary data, namely obtained directly from interviews. The research results show that motor vehicle fuel tax revenue after the increase in fuel prices in 2022 has increased by 11.28% to IDR 306,523,276,556 compared to the previous year 2021 of IDR 267,523,614,569, the contribution of motor vehicle fuel tax to regional taxes is also also increased after the increase in fuel prices in 2022, motor vehicle fuel tax contributed 25.24% for 2022 with medium criteria, compared to before the increase in fuel prices of 24.86% with medium criteria, the contribution in 2022 was greater than Compared with previous years, efforts to increase the contribution of motor vehicle fuel tax to regional tax revenues include increasing supervision, as well as monitoring and evaluating mandatory fuel collectors or providers.